FOOD HABITS AND CULTURE FACTORS IN PREGNANT ADOLESCENTS - Martinez, Cecilia Herrera; Nader, Jorge Daher; Mera, Yesica Pazmiño; Tumbaco, Rocio Fonseca; Morales, Vicky Narea (International Journal of Research -GRANTHAALAYAH, 2020)
Adequate eating habits during the gestation period of pregnant teenagers are of vital importance because this will affect the process of formation of the fetus at birth. If pregnant adolescents have an early pregnancy, the chances of a poor physiological maturity of the fetus are more likely to be executed, which makes it necessary to correctly implement the process of feeding during pregnancy, if possible eliminate all bad habit of feeding. The adolescent should seek the positive contribution of nutrients and food that contribute both to the fetus and the mother energy, which will be useful at birth. It should be noted that multiple studies in adolescent pregnant cultural factor food affects directly proportional to the time of feeding, in cases where the teenager is educated positively on their food is ingested foods balanced diet, eliminating all those foods that contain preservatives chemicals and processed foods that deteriorate the health of the pregnant woman. For the development of this research is to determine through the survey process the habits food and cultural factors of adolescent pregnant according to the sector, as well as also those relating theoretical to provide knowledge of the habits eating in adolescents pregnant, and also determine the nutrition of pregnant adolescents in relation to the gestational age of the patient according to the BMI, and identify the nutrition of pregnant women by developing an educational talk proposal in order to correct bad eating habits.